Peran Kegiatan Kreasso sebagai Upaya dalam Mempertahankan Kesenian Tradisional di Era Globalisasi - Desy Ade Liya; Yuhastina Yuhastina; Yosafat Hermawan Trinugraha (Mahesa Research Center, 2021)
The purpose of this study was to determine the role of Kreasso's activities as an effort to maintain traditional arts in the era of globalization. This research is a qualitative research, with a qualitative descriptive approach. Data analysis used Miles and Huberman analysis which consisted of 3 stages: (1) Data Reduction, (2) Data Display, and (3) Conclusion Drawing/ verification. This study uses the Structural-Functional theory proposed by Alfred Reginald Radcliffe Brown. The results of this study indicate that the existence of Kreasso's activities is able to grow students' dignity and concern for the social environment, especially traditional arts. This is evidenced by the participation of students who play an active role in the structural units of Kreasso's activities. Apart from that, it cannot be separated from the existence of activity actors, such as the Surakarta City Education Office as the person in charge of Kreasso activities; the Kreasso committee which generally consists of several divisions with different functions or roles, the teacher acts as a companion to the students; students act as participants with different assignments depending on the policies and authorities of each school. Each of them finds out how it works according to the function or role according to the position and position that cooperates with one another.